2022
DOI: 10.26480/bda.01.2022.01.07
|View full text |Cite
|
Sign up to set email alerts
|

GENETIC VARIABILITY AND ASSOCIATION AMONG YIELD AND YIELD COMPONENTS OF WHEAT GENOTYPES (Triticum Aestivum L.)

Abstract: The demand for wheat will be increased 60 % compared to existing by 2050 and the wheat productivity of Nepal is lower than world’s average productivity. Therefore, it is important to increase the yield potentiality of wheat. This research was conducted for the estimation of variability and association among yield and yield components of wheat. The experimental field was designed in alpha lattice design with 20 diverse wheat genotypes considering 12 important traits. In variability analysis, thousand kernel wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…It showed a negative correlation with TKW, and HI. A similar relationship of NSPS with SW and NGPS was found by Thapa, et al [25].…”
Section: Correlationsupporting
confidence: 86%
See 2 more Smart Citations
“…It showed a negative correlation with TKW, and HI. A similar relationship of NSPS with SW and NGPS was found by Thapa, et al [25].…”
Section: Correlationsupporting
confidence: 86%
“…It showed a significant negative correlation with TKW (-0.33) and a non-significant negative correlation with PH, GY, and HI. It was found that NGPS showed a positive and highly significant correlation with SW and NSPS [25]. Number of spikelets per spike showed a significantly high positive correlation with SL (0.44), SW (0.46), and NGPS (0.68) and a non-significant positive correlation with PH, GY, and SPMS.…”
Section: Correlationmentioning
confidence: 90%
See 1 more Smart Citation